2013
DOI: 10.1099/mic.0.062166-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of germination-arrest factor (GAF) production by Pseudomonas fluorescens WH6: identification of a gene cluster essential for GAF biosynthesis

Abstract: The genetic basis of the biosynthesis of the germination-arrest factor (GAF) produced by Pseudomonas fluorescens WH6, and previously identified as 4-formylaminooxyvinylglycine, has been investigated here. In addition to inhibiting the germination of a wide range of grassy weeds, GAF exhibits a selective antimicrobial activity against the bacterial plant pathogen Erwinia amylovora. We utilized the in vitro response of E. amylovora to GAF as a rapid screen for loss-offunction GAF phenotypes generated by transpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…The loss of GAF production in WH6-3 as a result of Tn5 insertion in prtR has been repeatedly confirmed in our laboratories (Kimbrel et al, 2010;Halgren et al, 2013). However, Burger et al (2000) observed that the loss of protease activity associated with mutation of prtR in P. fluorescens LS107d2 was temperature dependent.…”
Section: Biological Activity Of Wh6-3 Culture Filtratesmentioning
confidence: 63%
See 4 more Smart Citations
“…The loss of GAF production in WH6-3 as a result of Tn5 insertion in prtR has been repeatedly confirmed in our laboratories (Kimbrel et al, 2010;Halgren et al, 2013). However, Burger et al (2000) observed that the loss of protease activity associated with mutation of prtR in P. fluorescens LS107d2 was temperature dependent.…”
Section: Biological Activity Of Wh6-3 Culture Filtratesmentioning
confidence: 63%
“…As indicated in Fig. 1, the mutant WH6-3, which had lost the ability to produce GAF, had a Tn5 insertion in prtR at nt 417, within codon Asp139 (Halgren et al, 2013).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations